Interpretation as derealization - Šerpytytė, Rita (Religija ir kultūra, 2013)
The current status of ontology is not obvious, although it has become a fundamental discipline of the so-called “continental philosophy”. So it is worth asking, what are the main tendencies that represent the current “status” of ontology in the 20th–21st century philosophy. What main “trends” of post-Heideggerian philosophy represent these tendencies and determine the current status of ontology? In this article, the post-Heideggerian hermeneutical ontology is considered as a “trend” that embodies such transformative status of ontology. The question is: how hermeneutically oriented ontology treats the very notion of Being? What does it mean to interpret? What meaning to reality can give hermeneutically transformed ontology? How can we treat the reply of “new realisms” to hermeneutical ontology? These questions are considered in the context of Martin Heidegger, Gianni Vattimo, and “new realism” by discovering the “positive” nihilistic meaning of interpretation as derealization.